Characterization of the final graduation projects in Special Education at the University of Costa Rica from 2013 to 2023 - Solórzano Salas, Julieta (2025)
The bachelor’s degree research training is designed to guide future professionals as they embark on their journey in the field of education and develop the necessary skills to organize curriculum decisions and introduce innovations in interdisciplinary work. At the University of Costa Rica, the Final Graduation Project is integrated into a training process, with the support of an advisory committee, to provide a practical approach to developing research skills. The main objective of this study was to analyze and characterize 45 final graduation projects completed between 2013 and 2023 in the Special Education Degree program, to understand the nature of research training at this academic level. A systematic, descriptive documentary review was conducted using 8 categories of interest during the months of October 2023 to May 2024. Some of the key findings highlighted the importance of promoting interdisciplinary research among students, using various levels of Bloom's taxonomy, consistent with the topics being investigated, promoting the implementation of mixed methodologies in research, as well as incorporating under-analyzed thematic, such as work with families and the autonomy of adults with disabilities and other current topics related to inclusive educational spaces. The degree makes use of academic production, both in the courses and in future research in the Bachelor's Degree in Special Education. the key findings highlighted the importance of promoting interdisciplinary research among students, using various levels of Bloom's taxonomy, consistent with the topics being investigated, promoting the implementation of mixed methodologies in research, as well as incorporating under-analyzed tematics, such as work with families and the autonomy of adults with disabilities and other current topics related to inclusive educational spaces. The degree makes use of academic production, both in the courses and in future research in the Bachelor's Degree in Special Education.